Planeamento do turismo e análise do ciclo de vida : uma aplicaçao às ilhas da Madeira e de Fernando de Noronha - Alvares, Daniela (2009)
The aim of this paper is to describe a model for tourist areas and its application on two regions: Madeira lsland, in Portugal and Fernando de Noronha Island, in Brazil. Modelling tourism performance cvclos associated with planning and public investments cycles intends to be a contribution to the understanding of the tourism activity within a continuum process. This paper is based on the application of life cycle models for tourist destinations, specifically on Tourist Area Life Cycle theory, TALC (Butler, 1980) and on Lourenço’s model (Lourenço, 2003) for areas of urban expansion. Accordingly, it is possible to identify the stage of development of tourist destinations, as well as the behaviour of the model's variables along a thirty year life span. The idealized evolution obtained with the model will be compared with the tourist dynamics of both regions. The three components of the model named growth, planning and public investments of a tourism process can be modeled, as shown in the case studies presented. The use of the appropriate indicators to measure the activity is essential to validate the proposed tourism lifecycle modelling. The application of the model can be a relevant tool for tourism monitoring and allows for earlier awareness of negative impacts and therefore for higher success rates for tourísm activity management.